Online Teaching and Gender Bias - Sara Ayllón (Institute of Labor Economics (IZA), 2021)
I study the impact of online instruction on teaching evaluations at a higher education institution in Spain. Using a difference-in-differences approach, I show that in the semester when teaching moved online, female lecturers were evaluated more poorly than in previous semesters. The performance of male lecturers was not impacted by the new teaching environment, according to student opinion. I rule out several mechanisms: for example, poorer adaptation to online teaching by female lecturers, less experience in taught courses or student sorting. Additional results indicate that among the female lecturers, those who were younger and who did not have a permanent contract were those impacted most negatively. The bias was driven by male students and by low achievers (who were going to fail the course), and was particularly pronounced in Social Sciences. If the online environment keeps gaining in importance in higher education, the gender gap in teaching evaluations that I document is likely to have important direct and indirect effects on the career progression of women.
Keywords: J16; J71; I23; J45; 330; gender bias; online instruction; teaching evaluations; higher education; Spain